Government Expenditures, Health Outcomes and Marginal Productivity of Agricultural Inputs: The Case of Tanzania. (24th March 2014) - Allen, Summer; Badiane, Ousmane; Sene, Ligane; Ulimwengu, John
Abstract This paper examines the impact of health expenditures on agricultural labour productivity in order to inform the necessary policy decisions about targeting scarce public resources towards their most effective uses. We link health sector expenditures in rural Tanzania to health outcomes and agricultural labour productivity using data from the 2008 Household Budget Survey (10, 975 households) and the 2007/08 Agricultural Census (52, 594 households) across 113 districts in Tanzania. The results indicate that the marginal productivity of labour as well as land and fertilisers respond significantly to health expenditures. However, the magnitude of the response varies across types of disease, categories of expenditures and agricultural inputs. These findings suggest both the need and scope for targeting public expenditures in the health sector to achieve better agricultural growth outcomes.